Comparative analysis of historic predictions and actual global natural gas market trends for the period from 1997 to 2020 (Rudarsko-geološko-naftni zbornik, 2021)
An accurate prediction of energy indicators is critical for orientation in the energy market, and it could give direction for policymakers and market participants. The aim of this research was to examine the accuracy of projections of natural gas market indicators. This paper presents a comparative analysis of historic predictions and actual global natural gas movements in several segments, namely production, consumption, and regional import dependence, as well as forecasted and actual price movements. The goal of this paper is to compare projected and actual natural gas market indicators. Predictions of market movements 20 years into the future are very useful, but they do have certain limitations. Those limitations especially apply to goods whose prices are regional and linked to price movements of another good, as is the case with natural gas. External influences have a direct impact on production and consumption, and it is rather clear that changes in one of the fundamental factors entails and magnifies the error of further predictions. Despite that, predictions of global production and consumption have proven to be very accurate. Based on the research results, it could be emphasized that for strategical planning and policy-making purposes, the predictions of natural gas production, consumption, or even import independence could be considered with great certainty, while price assumptions in the case of natural gas have shown significant mismatching, therefore, should be very carefully perceived.